Implementasi Layanan Bimbingan Konseling dan Kontribusinya bagi Prestasi Belajar serta Perilaku Siswa Madrasah Ibtidaiyah: Implementation of Counseling Guidance Services and Its Contribution to Academic Achievement and Student Behavior at Madrasah Ibtidaiyah - Amelia, Rika; Rosadi, Adi; Sa'adiyah, Imas; Marwiji, Muh. Hasan (Sekolah Tinggi Agama Islam Kharisma Cicurug Sukabumi, 2024)
This study explores the implementation of guidance and counseling (GC) programs in Madrasah Ibtidaiyah (Islamic elementary schools) and their effects on students’ academic and behavioral outcomes. Conducted at MI Undruss Binangun using a qualitative case study approach, data were gathered through interviews with counselors, teachers, and students. The results show that GC programs contributed positively to student development—78% of students experienced a 15–20% improvement in academic grades, and 72% reported enhanced emotional regulation and conflict resolution skills. However, challenges such as limited time allocation, lack of parental awareness, and inadequate facilities hinder optimal implementation. Anchored in Bandura’s social learning theory, the study highlights the importance of structured guidance in shaping student behavior and achievement. To strengthen GC effectiveness, the study recommends integrating GC into the school curriculum, enhancing counselor training, and upgrading facilities. Future research should investigate digital-based GC models to broaden reach and accessibility. These findings support the advancement of holistic education in Islamic elementary schools and provide valuable insights for educators and policymakers aiming to improve student well-being and academic success.